Bismarck versus Beveridge: Which Unemployment Compensation System is More Prone to Labor Market Shocks? - Thomas Beissinger; Oliver Buesse (Institute for the Study of Labor (IZA), 2001)
Based on a model with imperfectly competitive labor and product markets the real consequences of labor market shocks for economies with either an earnings-related or flatrate unemployment compensation system are considered. A distinctive feature of the analysis is the comparison of both unemployment compensation systems in a two-country setting. It is demonstrated that the performance of a system with earnings-related or flat-rate unemployment benefits depends on whether the labor market shock is provoked in the home country or originates from abroad. We also point out how our results extend to two-tier unemployment compensation systems which differ with respect to the relative importance of earnings-related and flat-rate benefits.
Keywords: E24; F41; J23; J51; J65; 330; Earnings-related benefits; flat-rate benefits; unemployment; open economy; monopolistic competition; wage bargaining; Arbeitslosenversicherung; Soziale Sicherung; Vergleich; Schock; Arbeitsmarkttheorie; Lohnverhandlungstheorie; Monopolistischer Wettbewerb; Zwei-Länder-Modell; Beschäftigungseffekt; Arbeitslosigkeit; Theorie